Character Based Text for Development on V Grade Students of Elementary School - Burhanuddin Habibi Nasution; Abdul Rahman; Syahnan Daulay (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Amrullah, I., Imayah. (2019). Building students’ characters through character education and religiousity values in Syair Kitab Ta'lim Muta'allim. Jurnal AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 3(1), 53—65. doi: https://doi.org/10.21009/AKSIS.030106 Cohen, T.R., & Morse, L. (2014). Moral character: What it is and what it does. In A.P. Brief & B.M. Staw (Eds.), Research in Organizational Behavior. Elsevier. Retrieved from https://www.researchgate.net/publication/264000952_Moral_character_What_it_is_and_what_it_does Danandjaja, J. (1999). Folklor Indonesia, Ilmu Gosip, Dongeng, dan Lain-Lain. Jakarta: Grafiti. Dani, E.D. (2013). Pembentukan karakter anak melalui kegiatan mendongeng. .Jurnal Humanika, 17(1), 91—124. doi: 10.14710/humanika.17.1 Effendi, R. (2017, May 10). Hukum berat pembunuh keponakanku. Waspada, p. 5. Klein-Ezell, C., Ezell, D., Stanley, S.P., & Powell, S.E. (2014). Character education using children’s literature, puppets, magic tricks and balloon art. International Journal of Humanities and Social Science, 4(14), 1—15. Lickona, T. (2012). Character Matters. Jakarta: Bumi Aksara. Muslich, M. (2011). Pendidikan Karakter Menjawab Tantangan Krisis Multidimensional. Jakarta: Bumi Aksara. Purwahida, R. (2017). Interaksi sosial pada kumpulan cerpen Potongan Cerita di Kartu Pos karangan Agus Noor dan implikasinya terhadap pembelajaran sastra di SMA. Aksis: Jurnal Pendidikan Bahasa dan Sastra Indonesia 1(1). 118-134. doi: doi.org/10.21009/AKSIS.010107 Purwahida, R. (2018). Problematika Pengembangan Modul Pembelajaran Baca Tulis Anak Usia Sekolah Dasar. Aksis: Jurnal Pendidikan Bahasa dan Sastra Indonesia 2(1). 118-134. doi: doi.org/10.21009/AKSIS.020108. Sibarani, R. (2012). Local Wisdom: Hakikat, Peran, dan Metode Tradisi. Jakarta: ATL. Sugiyono. (2014). Metode Penelitian dan Pengembangan (Research and Depelopment: R&D). Bandung: Alfabeta. Sukmawan, S. (2016). Ekokritik Sastra: Menanggap Sasmita Arcadia. Malang: Universitas Brawijaya Press. Sulistyawati, Sri, Risnawaty, & Purba, N. (2015). Model pembentukan karakter bangsa terhadap siswa SMA dalam mengantisipasi pencegahan tindak pidana korupsi di Sumatera Utara. Laporan Penelitian Tahap I: Unggulan Perguruan Tinggi. Medan: UMN Al Washliyah. Syaifuddin, W. (2016). Pemikiran Kreatif & Sastra Melayu Tradisi. Yogyakarta: Gading. Turan, F., & Ulutas, I. (2016). Using storybooks as character education tools. Journal of Education and Practice, 7(15), 169—176. Wardani, Y. F. & Suhita, S. (2018). Nilai Pendidikan Karakter dalam Novel Rindu Karangan Tere Liye: Tinjauan Psikologi Karakter. Aksis: Jurnal Pendidikan Bahasa dan Sastra Indonesia 2(2). 247-273. doi: doi.org/10.21009/AKSIS.020207